Indigenous microorganisms from the corm of banana improve the growth and yield of three varieties of cucumber (Cucumis sativus L.) - Lasmini, Sri Anjar; Burhanuddin; Taiyeb, Asgar; Surya, I Komang (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: Cucumber (Cucumis sativus L.) is a type of vegetable that is widely consumed by the public. Cucumber production is still low due to cultivation systems that are not by standard operating procedures and low soil fertility. Therefore it is necessary to improve cultivation techniques through the use of quality seeds and fertilization. The study aimed to determine the effect of various concentrations of indigenous microorganisms from the corm of banana on the growth and yield of three varieties of cucumber. Methods: The study used a randomized block design with two factors: cucumber variety (Hercules, Mercy, Harmony) and concentration of indigenous microorganisms from banana corm (0, 200, 400, 600 ml/L). Each treatment was repeated three times with eight plants per plot, totaling 288 plants. Results: There was an interaction between cucumber varieties and microorganism concentrations. The Harmony variety with 600 ml/L of microorganisms showed the best results: plant height (162.03 cm), number of leaves (31.92), branches (3.57), fruits (10.58), and fruit weight (156.28 g). Conclusion: The Harmony variety and 600 ml/L concentration of indigenous microorganisms from banana corms significantly improved cucumber growth and yield. This method can reduce production costs by using easily available and cheap materials, decreasing reliance on expensive synthetic fertilizers.